2017
DOI: 10.1371/journal.pone.0175720
|View full text |Cite
|
Sign up to set email alerts
|

Tuber indicum shapes the microbial communities of ectomycorhizosphere soil and ectomycorrhizae of an indigenous tree (Pinus armandii)

Abstract: The aim of this study was to investigate the effect of an ectomycorrhizal fungus (Tuber indicum) on the diversity of microbial communities associated with an indigenous tree, Pinus armandii, and the microbial communities in the surrounding ectomycorhizosphere soil. High-throughput sequencing was used to analyze the richness of microbial communities in the roots or rhizosphere of treatments with or without ectomycorrhizae. The results indicated that the bacterial diversity of ectomycorhizosphere soil was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 59 publications
(75 reference statements)
8
60
3
Order By: Relevance
“…Root‐tip cutting, uniconazole treatment and inoculation of T. indicum reduced the microbial diversity in the rhizosphere soil of P. armandii seedlings, particularly on some indicators, including the observed species, Chao1 and Shannon indexes. Our previous study found that inoculation of T. indicum decreased microbial diversity in the rhizosphere soil of P. armandii seedlings under the same conditions (Li et al , ). Of all the major bacterial communities detected, three phyla, namely Proteobacteria, Actinobacteria and Chloroflexi, were dominant in all samples.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Root‐tip cutting, uniconazole treatment and inoculation of T. indicum reduced the microbial diversity in the rhizosphere soil of P. armandii seedlings, particularly on some indicators, including the observed species, Chao1 and Shannon indexes. Our previous study found that inoculation of T. indicum decreased microbial diversity in the rhizosphere soil of P. armandii seedlings under the same conditions (Li et al , ). Of all the major bacterial communities detected, three phyla, namely Proteobacteria, Actinobacteria and Chloroflexi, were dominant in all samples.…”
Section: Discussionmentioning
confidence: 80%
“…Alphaproteobacteria and Deltaproteobacteria (both in the phylum Proteobacteria) were found to be more abundant in the rhizosphere soil of root tip‐cut or 10 mg l −1 uniconazole‐treated colonized seedlings than in control rhizosphere soil. Previous studies also found that α‐Proteobacteria and γ‐Proteobacteria comprised the predominant components of the bacterial communities of truffles (Barbieri et al , ; Vahdatzadeh et al , ; Li et al , ). Previous studies have demonstrated that Pseudomonas fluorescens (Proteobacteria) improved the establishment and functioning of ectomycorrhizal symbiosis (Dominguez et al , ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations